2016
DOI: 10.1002/lt.24610
|View full text |Cite
|
Sign up to set email alerts
|

Macrovascular invasion is not an absolute contraindication for living donor liver transplantation

Abstract: The indication of liver transplantation (LT) for the treatment of advanced hepatocellular carcinoma (HCC) is expanding. However, portal vein tumor thrombus (PVTT) has been still accepted as an absolute contraindication. We experienced an unexpectedly good prognosis in selected patients. Therefore, we tried to identify the prognostic factors after LT for HCC with major PVTT. Among 282 patients who underwent living donor liver transplantation (LDLT) for HCC from January 2009 to December 2013, 11 (3.9%) patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
62
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(66 citation statements)
references
References 20 publications
4
62
0
Order By: Relevance
“…Although absolute numbers were small, none of the patients with complete response to neoadjuvant treatment had HCC recurrence. This "oncologically favourable" outcome has been recently confirmed by several case series (19)(20)(21)(22). Of a total of 21 patients who underwent LT with macrovascular invasion, 8 patients developed HCC recurrence.…”
Section: Futility Rule #1: Extrahepatic Metastases and Macrovascular mentioning
confidence: 63%
See 1 more Smart Citation
“…Although absolute numbers were small, none of the patients with complete response to neoadjuvant treatment had HCC recurrence. This "oncologically favourable" outcome has been recently confirmed by several case series (19)(20)(21)(22). Of a total of 21 patients who underwent LT with macrovascular invasion, 8 patients developed HCC recurrence.…”
Section: Futility Rule #1: Extrahepatic Metastases and Macrovascular mentioning
confidence: 63%
“…Of a total of 21 patients who underwent LT with macrovascular invasion, 8 patients developed HCC recurrence. Overall survival after 5 years was 64% in the largest series of patients with angioinvasive HCC (20). Main portal vein invasion was identified as the single most important risk factor for HCC recurrence, whereas a score including alpha-fetoprotein (AFP) and protein induced by vitamin K absence/antagonist-II (PIVKA-II) was predictive for recurrence free survival.…”
Section: Futility Rule #1: Extrahepatic Metastases and Macrovascular mentioning
confidence: 99%
“…Furthermore, a PVTT below the second‐order branch is difficult to identify accurately on preoperative images, and there were few reports on the posttransplant prognoses of patients with PVTT below the second‐order branch. Lee et al reported that the level of PVTT affects tumor recurrence after LT . However, the result of this study is based on a small number of patients (n = 11).…”
Section: Discussionmentioning
confidence: 74%
“…However, in recent years, many transplant communities have sought to expand these conventional selection criteria to include patients with HCC for whom LT can prolong survival. However, there are few reports of post‐LT results according to the PVTT level . So, we sought to define the branch levels in which PVTT presence was acceptable in LT.…”
Section: Discussionmentioning
confidence: 99%
“…The differences in the number of listed patients and available grafts among regions, societies, and nations make it difficult to reach a worldwide consensus regarding the indications for liver transplantation for HCC, especially in the LDLT setting. Some centers strictly follow the Milan criteria, even for LDLT , while others have aggressively expanded the indications, even for those with macrovascular invasion .…”
Section: Introductionmentioning
confidence: 99%